2022
DOI: 10.1093/braincomms/fcac104
|View full text |Cite
|
Sign up to set email alerts
|

Network connectivity predicts effectiveness of responsive neurostimulation in focal epilepsy

Abstract: Responsive neurostimulation (RNS) is a promising treatment for drug-resistant focal epilepsy; however, clinical outcomes are highly variable across individuals. The therapeutic mechanism of RNS likely involves modulatory effects on brain networks; however, with no known biomarkers that predict clinical response, patient selection remains empiric. This study aimed to determine whether functional brain connectivity measured non-invasively prior to device implantation predicts clinical response to RNS therapy. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Fan et al looked at functional connectivity across various spatial scales, including global, hemispheric, and lobar, after spectral decomposition of patient ECoG data obtained from RNS. Fan et al demonstrated that increased baseline functional network connectivity was associated with improved clinical outcomes, as measured by percent change in self-reported seizure frequency in the most recent year of clinic visits, compared to prior to RNS device implantation [ 54 ]. More specifically, they identified that increased global functional connectivity in the alpha frequency band was correlated with seizure frequency reduction (P = 0.010).…”
Section: Rns Modulation Of Epileptic Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan et al looked at functional connectivity across various spatial scales, including global, hemispheric, and lobar, after spectral decomposition of patient ECoG data obtained from RNS. Fan et al demonstrated that increased baseline functional network connectivity was associated with improved clinical outcomes, as measured by percent change in self-reported seizure frequency in the most recent year of clinic visits, compared to prior to RNS device implantation [ 54 ]. More specifically, they identified that increased global functional connectivity in the alpha frequency band was correlated with seizure frequency reduction (P = 0.010).…”
Section: Rns Modulation Of Epileptic Networkmentioning
confidence: 99%
“…RNS currently targets 1–2 foci in order to treat seizures, in approaching epilepsy as a focus-based disorder. However, as described above, studies are now showing that neuromodulatory devices exert their therapeutic effects through network disruption, not focus disruption [ 54 ]. Using this information, we can inform RNS target placement to address key nodes in the epileptogenic network, allowing for improved seizure control.…”
Section: Improving Seizure Prediction and Controlmentioning
confidence: 99%
“…For nearly one-third of refractory patients, seizures cannot be fully controlled by antiepileptic drugs [ 2 ]. In order to achieve seizure freedom for those patients, clinical treatment including surgical resection, laser ablation and responsive neurostimulation (RNS) of epileptic tissue are considered during intracranial electroencephalography (iEEG) monitoring [ 3 , 4 , 5 ]. However, effective treatment depends on accurate localization of epileptic tissue, which is a major challenge in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent article in Brain Communications, Fan et al . 7 provide a fascinating and well-constructed analysis of resting-state magnetoencephalography (MEG) data collected from patients who went on to have RNS device implantations and show that FC measures could provide a patient-specific biomarker for providing an a priori expected RNS responsiveness pre-implantation ( Fig. 1 ).…”
mentioning
confidence: 99%
“… The main findings of Fan et al . 7 are summarized in this figure. Thirty-one patients underwent MEG ( left ) before implantation of a RNS device.…”
mentioning
confidence: 99%